Quelle éthique pour quelle Église ? - Collaud, Thierry (Revue d'éthique et de théologie morale, 2025)
On the occasion of his farewell lecture, the author looks back at his approach to ethics, which has led him to reflect on the way in which the Catholic Church should express its morality, less as a normative discourse than as a way of presenting itself as a fraternal community, the Body of Christ. Seeking the good life of the Church means trying to describe its virtues, and we have chosen three of them: 1) Coherence, which is thought of in musical terms as polyphony developing around the axis of a cantus firmus. 2) Habitation, which describes the just relationship to the place between the insufficiency of an uninvolved presence and the excess of unwarranted appropriation. 3) Finally, humility as self-emptying which becomes the virtue that allows grace to shine through and makes the Church beautiful and gracious.